(untitled) (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2013)
Biopesticides are the formulated form of active ingredients based on microorganisms such as bacteria, viruses, fungi, nematodes or naturally-occurring substances, including plant extracts and semiochemicals (e.g. insect pheromones). Application of biopesticides is still limited to only a few percent of all pesticides used for crop protection. There are many factors contributing to that situation, such as expensive production methods, poor storage stability, susceptibility to environmental conditions, efficacy problems, etc. Some of these problems can be overcome by formulation improvements. With many pressures on product performance formulation is becoming the most important area to enhance and extend the activity of biopesticides. In this paper we reviewed different types of biopesticides existing on the market and discussed possibilities for their application and current status. The expected future trends in formulation development of biopesticides are explained.